Journey to the Alamo - Cuate, Melodie A. (Lubbock, Tex. : Texas Tech University Press, 2006)
When the new seventh-grade history teacher brings a mysterious trunk to class, Jackie, Hannah, and her brother Nick find themselves transported to the Alamo, where they experience the famous siege first-hand.
Keywords: Time travel -- Fiction; Schools -- Fiction; Alamo (San Antonio, Tex.) -- Juvenile fiction. -- Siege, 1836; Texas -- Juvenile fiction. -- History -- Revolution, 1835-1836; Alamo (San Antonio, Tex.) -- Fiction. -- Siege, 1836; Texas -- Fiction. -- History -- Revolution, 1835-1836; Fiction